Alki, birthplace of Seattle [videorecording (VHS)] - Bullert, B. J., 1955-; Denny, Brewster C.; Rasmussen, James; Buerge, David M. (Distributed by Wehman Video, 1997)
Examines the arrival of the Denny Party on the shores of Alki in November 1851, marking the beginning of an era that would change the landscape and the lives of the native Duwamish forever. Told from the perspective of pioneer descendant Brewster Denny, James Rasmussen, a Duwamish descendant of Chief Seattle, and historian David Buerge.